Implementasi Perawatan Spiritual Pada Pasien Kanker Kolorektal Di Ruang Rawat Inap: Laporan Kasus - Amatullah, Dhiyaa Ulhaq; Mambang Sari, Citra Windani; Agustina, Hana Rizmadewi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Colorectal cancer is the second leading cause of cancer-related deaths worldwide and has a negative impact on the quality of life of cancer sufferers. In cancer patients, meeting spiritual needs is very important. Fulfilling spiritual needs is related to the quality of life of cancer patients. Objective: To describe how to providing spiritual care for patients with colorectal cancer. Method: This research uses descriptive research with a case report approach. The subjects in this study were patients with a medical diagnosis of colorectal cancer. The intervention provided is in the form of providing spiritual needs. This research has implemented research with human subjects to maintain the ethics of the research carried out. Results: There was an increase in the client's spiritual aspect after the intervention. Additionally, providing for spiritual needs has a positive impact on clients. Discussion: Providing spiritual care has an impact on the client's calm, the client's self-acceptance, the client's eating and life goals, then the client's condition towards the end and the client's hopes for his illness. Conclusion: Providing spiritual care has benefits in improving the quality of life of cancer sufferers. Nurses are expected to be able to provide spiritual care to patients in accordance with the patient's religion by facilitating patients in carrying out their worship